Embryonic Cell Grafts in a Culture Model of Spinal Cord Lesion: Neuronal Relay Formation Is Essential for Functional Regeneration - Tscherter, Anne; Heidemann, Martina; Kleinlogel, Sonja; Streit, Jürg (Frontiers in Cellular Neuroscience, 2016)
Presently there exists no cure for spinal cord injury. However, transplantation of embryonic tissue into spinal cord lesions resulted in axon outgrowth across the lesion site and some functional recovery, fostering hope for future stem cell therapies. Although in vivo evidence for functional recovery is given, the exact cellular mechanism of the graft support remains elusive: either the grafted cells provide a permissive environment for the host tissue to regenerate itself or the grafts actually integrate functionally into the host neuronal network reconnecting the separated spinal cord circuits. We tested the two hypotheses in an in vitro spinal cord lesion model that is based on propagation of activity between two rat organotypic spinal cord slices in culture. Transplantation of dissociated cells from E14 rat spinal cord or forebrain re-established the relay of activity over the lesion site and, thus, provoked functional regeneration. Combining patch-clamp recordings from transplanted cells with network activity measurements from the host tissue on multi-electrode arrays we here show that neurons differentiate from the grafted cells and integrate into the host circuits. Optogenetic silencing of neurons developed from transplanted embryonic mouse forebrain cells provides clear evidence that they replace the lost neuronal connections to relay and synchronize activity between the separated spinal cord circuits. In contrast, transplantation of neurospheres induced neither the differentiation of mature neurons from the grafts nor an improvement of functional regeneration. Together these findings suggest, that the formation of neuronal relays from grafted embryonic cells is essential to re-connect segregated spinal cord circuits.